Construct validity of eoSim – a low-cost and portable laparoscopic simulator. - Mansoor, Saira Mauland; Våpenstad, Cecilie; Mårvik, Ronald; Glomsaker, Tom; Bliksøen, Marte (Minimally Invasive Therapy & Allied Technologies, 2020)
Purpose: To examine the construct validity of the low-cost, portable laparoscopic simulator eoSim using motion analysis. Material and methods: Novice and experienced surgeons (≤ 100 and >100 laparoscopic procedures performed, respectively) completed four tasks on the eoSim using the SurgTrac software: intracorporeal suture and tie, tube ligation, peg capping and precision cutting. The following metrics were recorded: Time to complete task, distance traveled, handedness (left- versus right hand use), time off-screen, distance between instrument tips, speed, acceleration and motion smoothness. Results: Compared to novices (n = 22), experienced surgeons (n = 14) completed tasks in less time (p ≤.025), except when performing peg capping (p =.052). On all tasks, they also scored lower on the distance metric (p ≤.001). Differences in handedness (left hand compared between groups, right hand compared between groups) were found to be significant for three tasks (p ≤.025). In general, the experienced group made greater use of their left hand than the novice group. Conclusion: The eoSim can differentiate between experienced and novice surgeons on the tasks intracorporeal suture and tie, tube ligation and precision cutting, thus providing a convenient method for surgical departments to implement testing of their surgeons' basic laparoscopic skills.